Children, Families, Schools, and Communities - Giovannini, Joan (Open textbook library., 2024)
Children, Families, Schools, and Communities is an introductory text in the field of Child and Family Studies. It provides a lens for understanding the evolving definition of “family” through socially constructed and ecological theory frameworks. It promotes strategies for culturally sustaining and deeply collaborative relationships between families, schools, and communities through the use of home-grown advocacy strategies based on community-driven data. Children, Families, Schools, and Communities is an adapted OER text from Rebecca Laff’s and Wendy Ruiz’s Child, Family, and Community.